Penerapan Problem Based Learning untuk Meningkatkan Keterampilan Menulis Teks Prosedur Siswa Kelas VII SMP Muhammadiyah PK Surakarta Tahun 2023/2024: Implementation of Problem Based Learning to Improve the Writing Skills of Procedure Texts of Students in Grade VII of SMP Muhammadiyah PK Surakarta in 2023/2024 - Nurrochmat, Dimas; Prabowo, Andi Haris; Aryanto (Universitas Nusantara PGRI Kediri, 2024)
This classroom action research explored the efficacy of Problem Based Learning (PBL) in enhancing procedural text writing skills among 32 seventh-grade students at SMP Muhammadiyah PK Kottabarat Surakarta. The study employed a cyclical approach, encompassing a Pre-Cycle and two subsequent Cycles, utilizing observation, tests, and documentation for data collection. Both qualitative and quantitative analyses were conducted to assess the impact of the PBL model. The findings revealed a substantial improvement in students' procedural text writing abilities. Qualitatively, the PBL implementation fostered increased engagement from both teachers and students, manifesting in heightened cooperation and enthusiasm during learning activities. Quantitatively, a progressive increase in student writing scores was observed. The average score rose from 72.5% in the Pre-Cycle to 77.81% in Cycle I, and further to 86.09% in Cycle II, indicating a total average score improvement of 13.59%. This data strongly suggests that the PBL model effectively promotes the development of procedural text writing skills, demonstrating its potential as a valuable pedagogical tool in the classroom.